2017
DOI: 10.1111/jocn.13951
|View full text |Cite
|
Sign up to set email alerts
|

Management of newly diagnosed atrial fibrillation in an outpatient clinic setting—patient's perspectives and experiences

Abstract: This study demonstrates some lack of patient-centred care and an absence of tailored patient AF-related education. Furthermore, the study highlights the need for and importance of active patient involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 46 publications
(45 reference statements)
3
46
0
Order By: Relevance
“…We believe that our study ndings have signi cant implications for clinical practice and policy. Our ndings regarding the knowledge de cit of patients being the primary reason for minimal involvement of patients in decision-making regarding the treatment options for stroke prevention were consistent with previous studies (23,24,36). Educational interventions by health professionals are highly recommended to the public, especially aimed at patients with AF and their caregivers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We believe that our study ndings have signi cant implications for clinical practice and policy. Our ndings regarding the knowledge de cit of patients being the primary reason for minimal involvement of patients in decision-making regarding the treatment options for stroke prevention were consistent with previous studies (23,24,36). Educational interventions by health professionals are highly recommended to the public, especially aimed at patients with AF and their caregivers.…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have reached similar conclusions. Thrysoee et al reported patients in their study did not understand the association between AF, stroke, and anticoagulation so they were not actively involved in the decision-making process and took the medication as prescribed by the physician (36). In addition, a systematic review previously reported that patients' high level of con dence in physicians' professional knowledge and training was one of the reasons for decision delegation (24).…”
Section: Discussionmentioning
confidence: 99%
“…16 Other work has found that patients were uncertain what AF was before and after outpatient cardiology clinic appointments. 17 They also had difficulty understanding why they were treated with anticoagulation and why treatment was recommended lifelong. 17 Older patients, in particular, may have a poor understanding of AF.…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…17 They also had difficulty understanding why they were treated with anticoagulation and why treatment was recommended lifelong. 17 Older patients, in particular, may have a poor understanding of AF. 18 This may be a key barrier to accepting anticoagulation treatment and to future treatment adherence, which is imperative for stroke risk reduction.…”
Section: Findings In Relation To Other Studiesmentioning
confidence: 99%
“…Generally speaking, a new diagnosis of AF can be overwhelming 4. Inevitably, patients will be bombarded at their initial clinic visit with a tremendous amount of new information.…”
mentioning
confidence: 99%